Porphyria in pregnancy with exacerbation after delivery due to COVID-19 - Jartych, Aleksandra; Michalska, Karolina; Oleksak, Izabela; Sauermann, Janusz; Jamroz-Wiśniewska, Anna; Rejdak, Konrad (Journal of Education, Health and Sport, 2024)
We present a case of acute intermittent porphyria (AIP) diagnosed in a pregnant woman with subsequent exacerbation after delivery due to COVID-19 infection. The patient’s symptoms manifested with acute neurovisceral attacks - abdominal pain followed by flaccid quadriparesis, sensory disturbances, hypertension and disturbance in electrolyte levels. The blood plasma test and a 24-hour urine collection revealed increased levels of urine porphobilinogen, 5-aminolevulinic acid and uroporphyrins, which led to the diagnosis of AIP. The patient received i.v. human hemin with positive outcome. After delivery she was again admitted to the hospital due to abdominal pain and trunk hyperesthesia that occurred after a mild course of COVID-19 infection. The second administration of human hemin led to the improvement of the patient's condition. The aim of this case report is to indicate that even with severe risk factors of AIP such as infection and pregnancy, proper diagnostics can increase the chance of quick recovery.